Metals accumulation of tropical shrub melastoma malabathricum L. (Melastomataceae) populations and their relation to soil edaphic factor - Norshahida Saberi,; Mohd Izuan Effendi Halmi,; Muhammad Saiful Ahmad Hamdani,; Noor Amalina Ramle,; Khairil Mahmud, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Melastoma malabathricum L. (Melastomataceae) is a widely distributed tropical shrub that grows in Southeast Asia. Recent research found that M. malabathricum has a bioremediatory potential that can accumulate high concentrations of toxic metals such as Al, Pb, As, and Cr. Thus, this study aimed to investigate the metal hyperaccumulation in M. malabathricum from various populations and their relation to soil edaphic factors. We collected mature leaves and soils of M. malabathricum from 15 different populations in Negeri Sembilan, Selangor, and Pahang in Peninsular Malaysia. These 15 populations consist of lowland forests, dump sites, riparian, oil palm and rubber plantations, paddy fields, and mining sites. We found that M. malabathricum accumulated high concentrations of Al (3.45±1.58 to 8.697±1.61 mg g-1) followed by Fe (1.02±0.02 to 1.07±0.04 mg g-1), Pb (0.013±0.001 to 0.016±0.001 mg g-1), As (0.008±0.005 to 0.23±0.004 mg g-1), and Cr (0.005±0.0003 to 0.02±0.01 mg g-1). The highest concentration of soil Al was 85.95±5.00 mg g-1, Fe with 69.960±7.47mg g-1, Pb with 0.192±0.03 mg g-1, As with 0.156±0.06 mg g-1 and Cr with 0.133±0.03 mg g-1. We found no significant association between high foliar metal concentrations of the metals (Al, Pb, As & Cr) with the soil chemical properties but some soil metal elements were intercorrelated with foliar metal concentrations. Understanding the potential of M. malabathricum in accumulating high levels of metal elements, provides useful information for phytoremediation works. Further research is required to investigate the mechanism uptake and tolerance of heavy metals in M. malabathricum.